Demonstration of efficient vertical and venereal transmission of dengue virus type-2 in a genetically diverse laboratory strain of Aedes aegypti. - Irma Sánchez-Vargas; Laura C Harrington; Jeffrey B Doty; William C Black; Ken E Olson (Public Library of Science (PLoS), 2018)
Aedes aegypti is the primary mosquito vector of dengue viruses (DENV; serotypes 1-4). Human-mosquito transmission cycles maintain DENV during epidemics but questions remain regarding how these viruses survive when human infections and vector abundance are minimal. Aedes mosquitoes can transmit DENV within the vector population through two alternate routes: vertical and venereal transmission (VT and VNT, respectively). We tested the efficiency of VT and VNT in a genetically diverse laboratory (GDLS) strain of Ae. aegypti orally infected with DENV2 (Jamaica 1409). We examined F1 larvae from infected females generated during the first and second gonotrophic cycles (E1 and E2) for viral envelope (E) antigen by amplifying virus in C6/36 cells and then performing an indirect immunofluorescence assay (IFA). RT-PCR/nested PCR analyses confirmed DENV2 RNA in samples positive by IFA. We observed VT of virus to larvae and adult male progeny and VNT of virus to uninfected virgin females after mating with males that had acquired virus by the VT route. We detected no DENV2 in 30 pools (20 larvae/pool) of F1 larvae following the first gonotrophic cycle, suggesting limited virus dissemination at 7 days post-infection. DENV2 was detected by IFA in 27 of 49 (55%) and 35 of 51 (68.6%) F1 larval pools (20 larvae/pool) from infected E2 females that received a second blood meal without virus at 10 or 21 days post-infection (E2-10d-F1 and E2-21-F1), respectively. The minimum filial infection rates by IFA for E2-10d-F1 and E2-21d-F1 mosquitoes were 1:36 and 1:29, respectively. The VNT rate from E2-10d-F1 males to virgin (uninfected) GDLS females was 31.6% (118 of 374) at 8 days post mating. Twenty one percent of VNT-infected females receiving a blood meal prior to mating had disseminated virus in their heads, suggesting a potential pathway for virus to re-enter the human-mosquito transmission cycle. This is the first report of VNT of DENV by male Ae. aegypti and the first demonstration of sexual transmission in Aedes by naturally infected males. Our results demonstrate the potential for VT and VNT of DENV in nature as mechanisms for virus maintenance during inter-epidemic periods.